Improving the Optical Properties of PVA/PEG Blend Doped with BaTiO3 NPs. Issue 1 (July 2021) - Mohammed, Batool; Ahmed, Hind; Hashim, Ahmed
Abstract: In this paper, synthesis in PVA/PEG/BaTiO3 new nanocomposites was investigated to use in various optoelectronics fields. The PVA/PEG/BaTiO3 nanostructures prepared from PVA/PEG blend with various ratios of BaTiO3 NPs. The optical characteristics of synthesized PVA/PEG/BaTiO3 nanostructures have studied. Results indicated that the optical characteristics of PVA/PEG improved as BaTiO3 NPs ratio increase, this behavior makes it may be used in different electronics and photonics fields.